Finnish professional criminals and their organisations in the 1990SA - Junninen, Mika (2008)
This article concentrates on Finnish professional criminals and their organisations in Finland and in cross-border crime operations. It is based on qualitative empirical material. It focus on 14 different Finnish groups active in the 1990s in smuggling (alcohol, tobacco and drugs), and/or procuring prostitutes, and/or handling stolen goods. The objective of the study was twofold: 1) to gather collective information about the world of the Finnish professional criminals by studying the personal characteristics of the group members, the crimes they commit, and the structures of the criminal groups, 2) to compare differences and similarities of professional criminals and organised crime groups in Finland and abroad. The study clearly shows, that Finnish professional criminal groups are loosely structured networks that based on trade relations between the participants. The operational time of the groups is short and laundering of profits is not planned beforehand. The comparison of stud